Effectiveness of Brief Solution-Focused Therapy on Quality of Life and Hope in Mothers of Children with Cancer - Iranmanesh, Aida; Zohrei, Moslam; Babaei, Roya; Shahmiri Sehrangi, Somayeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: This study aimed to examine the effectiveness of Brief Solution-Focused Therapy (BSFT) in reducing depression and improving quality of life among mothers of children with cancer. Methods and Materials: The research utilized a quasi-experimental design with a pre-test/post-test control group. The statistical population included all mothers of children with cancer in Kerman, Iran, during 2023. Thirty participants were selected through convenience sampling and randomly assigned to experimental (n = 15) and control (n = 15) groups. The experimental group received eight sessions of BSFT, each lasting approximately 60 minutes. Data were collected using the Beck Depression Inventory and the WHOQOL-BREF Quality of Life Questionnaire. Data analysis was conducted using SPSS-23, employing descriptive statistics, the Shapiro-Wilk test for normality, Box’s M test for homogeneity of covariance matrices, and analysis of covariance (ANCOVA) for inferential comparisons. Findings: ANCOVA results revealed significant differences between the experimental and control groups in both dependent variables. The BSFT intervention significantly reduced depression scores (F(1,26) = 91.61, p < .001, η² = .779) and significantly improved quality of life scores (F(1,26) = 51.88, p < .001, η² = .666) after controlling for pre-test scores. The interaction effects between pre-test scores and treatment were non-significant, indicating homogeneity of regression slopes and validating the ANCOVA assumptions. Conclusion: The results demonstrate that Brief Solution-Focused Therapy is a highly effective short-term psychological intervention for alleviating depressive symptoms and enhancing quality of life in mothers of children with cancer. Given its time-efficient structure and focus on personal strengths and solution-building, BSFT can be a valuable component of supportive care in pediatric oncology settings.